The Role of AMPS in Parkinson’s Disease Management: Scoping Review and Meta-Analysis - Roberto Tedeschi; Danilo Donati; Federica Giorgi (Bioengineering)
Background: Automated Mechanical Peripheral Stimulation (AMPS) is emerging as a potential therapeutic tool for managing motor and non-motor symptoms in individuals with Parkinson’s disease (PD), particularly in terms of improving gait, balance, and autonomic regulation. This scoping review aims to synthesize current evidence on AMPS’s effectiveness for these outcomes. Methods: A review was conducted on MEDLINE, Cochrane Central, Scopus, PEDro, and Web of Science. Studies were included if they examined AMPS interventions for PD patients and reported outcomes related to gait, balance, neurological function, or autonomic regulation. Data extraction focused on study design, intervention details, sample characteristics, and key outcomes. Quality was assessed using the PEDro and RoB-2 scales. Results: Six randomized controlled trials met the inclusion criteria. AMPS consistently improved gait kinematic parameters, including step length and gait velocity, and reduced gait asymmetry. In addition, increased brain connectivity between motor regions was correlated with enhanced gait speed, suggesting neuroplastic effects. Some studies reported improved autonomic regulation, with enhanced heart rate variability and blood pressure stability. However, limitations such as small sample sizes, short follow-ups, and varied protocols affected the consistency of the findings. Conclusions: AMPS shows potential as an adjunct therapy for PD, improving gait, balance, and possibly autonomic function. These preliminary findings will support further research into establishing standardized protocols, confirming long-term efficacy, and exploring AMPS’s impact on non-motor symptoms. With robust evidence, AMPS could complement existing PD management strategies and improve patient outcomes.